Actualization of Manquliy's Learning Model in the Transmission of Science - Ngatipan Ngatipan; Abdurrahman Assegaf; Sumedi Sumedi (AL-ISHLAH: Jurnal Pendidikan, 2022)
Manquliy learning is a form of variation in the transmission of knowledge in classical Islamic scholarship. Manqūliy learning is a characteristic as well as a feature of the Islamic education system that is not shared by others. In addition, mutawâtir manquliy learning is believed to be a mechanism in obtaining knowledge, so that a person's knowledge is tested for validity and can be accounted for morally and scientifically. However, in its development the manquliy learning mindset continues to grow, not only in essential matters, but also in other matters, so that there are pros and cons between parties regarding who is the holder of scientific authority and how science can be said to be manquliy. The purpose of this paper is to try to raise the phenomenon of the actualization of LDII manqūliy learning in the education system and da'wah of their organization. This research is a qualitative study. The results show that manquliy learning as a process of transmitting knowledge is no longer limited to giving authority to a person (student) in the aspect of the mechanism of acquiring knowledge, but must include 3 processes at once, namely Pemanql the holder of knowledge authorization, manqūl material development (internalization) and monitoring and realization of the output of the learning. Then, the authorization of manquliy learning is implemented in 2 steps, namely the mainstream monopoly and the hegemony of dalil authorization.